WASOG Clinical Trial Endpoint Task Force: Executive Summary - Baughman, Robert P.; Lower, Elyse E.; Culver, Daniel A.; Judson, Marc A.; Wells, Athol U. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Over the past few years, an increased number of clinical trials have been performed evaluating specific therapies for pulmonary and cardiac sarcoidosis. However, a lack of consensus remains for appropriate clinical trial endpoints. In 2024, the World Association of Sarcoidosis and Other Granulomatous disease (WASOG) established a clinical trial endpoint Task Force to update the 2011 WASOG Task Force. This initiative was spearheaded by five sarcoidosis specialists (RPB, EEL, DAC, MAJ, AUW) and enlisted a total of 55 stakeholders, including 37 health care providers, 14 industry representatives, and 4 patients. In March 2025, 46 stakeholders participated in a one-day meeting which included twenty focused talks regarding clinical trial endpoints for pulmonary and cardiac sarcoidosis trials. A compilation of individual talk summaries was prepared and distributed to all stakeholders, including those unable to attend the meeting. Based on feedback from all stakeholders, the team leaders developed a series of statements reflecting the presentations and discussions with subsequent anonymous voting by all stakeholders. The majority of the voters endorsed thirteen specific clinical trial endpoint statements: two evaluating overall trial design, seven regarding pulmonary sarcoidosis, and four discussing cardiac sarcoidosis.